The Sociology of Humanist, Spiritual, and Religious Practice in Prison: Supporting Responsivity and Desistance from Crime - Jeff B. Duncan; Tom P. O’Connor (Religions, 2011)
This paper presents evidence for why Corrections should take the humanist, spiritual, and religious self-identities of people in prison seriously, and do all it can to foster and support those self-identities, or ways of establishing meaning in life. Humanist, spiritual, and religious (H/S/R) pathways to meaning can be an essential part of the evidence-based responsivity principle of effective correctional programming, and the desistance process for men and women involved in crime. This paper describes the sociology of the H/S/R involvement of 349 women and 3,009 men during the first year of their incarceration in the Oregon prison system. Ninety-five percent of the women and 71% of the men voluntarily attended at least one H/S/R event during their first year of prison. H/S/R events were mostly led by diverse religious and spiritual traditions, such as Native American, Protestant, Islamic, Wiccan, Jewish, Jehovah Witness, Latter-day Saints/Mormon, Seventh Day Adventist, Buddhist, and Catholic, but, increasingly, events are secular or humanist in context, such as education, yoga, life-skills development, non-violent communication, and transcendental meditation groups. The men and women in prison had much higher rates of H/S/R involvement than the general population in Oregon. Mirroring gender-specific patterns of H/S/R involvement found in the community, women in prison were much more likely to attend H/S/R events than men.